The Role of Language in Manipulation Class in Parasite (2019) - Auriza Yulianto, Cahya Happy; Herlyna, Herlyna; Ramadhina, Retno (STIBA IEC JAKARTA, 2025)
Language is employed in building human interaction, especially in class-stratified situations. Language is examined as a form of class manipulation through speech style and politeness strategy in Parasite (2019). Theory can categorize speech and politeness, but their employment tactically is likely to differ in real-life situations as well as in narrative. The way people speak in different social settings has long been a focus in areas like pragmatics and sociolinguistics, and Parasite offers a rich example of how language reflects deeper social structures. Drawing on Martin Joos’s speech style theory and Brown and Levinson’s politeness theory, the results recognize that the Kim family employs a formal and consultative style to claim social legitimacy and that intimate speech achieves emotional bonding. They also employ positive politeness for rapport-building, negative politeness for expressing deference, and bald-on-record or off-record strategies to achieve control and hide agendas. In general, the study reaffirms that language in Parasite is a tactical instrument of class mobility, manipulation, and social scheming